Analysis of the sanitation hygiene conditions of DAMIU handlers in Bantan District, Bengkalis Regency - Rika Mianna; Ismawi Ismawi; Rendi Randika (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Clean water is one of the vital human needs that must be considered hygiene sanitation. At this time most people use refilled water to meet their daily needs, if sanitation is not guaranteed, it can cause disease. One of the sanitary hygiene that needs to be considered at the Refill Drinking Water Depot (DAMIU) is the sanitation hygiene of the workers. This study aims to determine the sanitary hygiene conditions of DAMIU workers in Bantan District, Bengkalis Regency, where based on the results of the preliminary study there are still many DAMIU workers who ignore their sanitary hygiene. Method: This research is a descriptive study to describe the sanitation hygiene conditions of DAMIU workers. The data in this study were obtained by direct observation and interviews with 12 DAMIU. Results: The results showed that all workers were in good health and free from infectious diseases and were not carriers of disease germs, all workers did not use clean and tidy work clothes, 92 percent did not have their health checked regularly (at least once a year), 75 percent did not wash hands with soap and running water every time they serve consumers, 58 percent each does not have a training certificate and have hygienic behavior. It is hoped that the relevant agencies can follow up on this situation so that people can consume healthy water Conclusion: Based on the results of the study it can be concluded that DAMIU handlers are in good health and free from infectious diseases, however, they still behave unhygienic, especially in using clean and tidy work clothes, do not have regular health checks and do not wash their hands with soap every time they serve consumers.